Exploring how health behaviours are supported and changed in people with severe mental illness: A qualitative study of a cardiovascular risk reducing intervention in Primary Care in England. Issue 3 (13th April 2020) - Hassan, Suzan; Ross, Jamie; Marston, Louise; Burton, Alexandra; Osborn, David; Walters, Kate
Abstract : Objectives: This study explored how health behaviours were supported and changed in people with severe mental illness by primary health care professionals trained in delivering behaviour change techniques (BCTs) within a cardiovascular disease risk reducing intervention. Design: Secondary qualitative analysis of 30 staff and patient interviews. Methods: We mapped coded data to the BCT Taxonomy (version 1) to identify BCT application. Thematic analysis was conducted to explore the barriers and facilitators of supporting and changing health behaviours. Themes were then interpreted using the Capability, Opportunity, Motivation, and Behaviour model to gain greater explanation behind the processes. Results: Twenty BCTs were identified. Staff and patients perceived that health behaviours were commonly affected by both automatic and reflective motivation, sometimes in turn affected by psychological capability, social, and physical opportunity. Staff and patients suggested that motivation was enhanced by both patient and staff ability to observe health benefits, in some cases patients' health knowledge, mental health status, and social support networks. It was suggested that engaging in/sustaining healthy behaviours was influenced by physical opportunities to engrain behaviours into routine. Conclusions: According to staff and patients, health behaviour change in this population was driven by complex processes. It was suggested that capability, opportunity, and motivation were in some cases enhanced by BCTs, but variable. Behaviour change may be optimized by individualized behavioural assessments, identifying drivers of behaviour and applying a range of BCTs may help to target individual needs. Patient peer‐led approaches, techniques to encourage awareness of visible success, and normalizing health behaviours may increase behaviour change. Statement of contribution What is already known on this subject? Poorer health behaviours may contribute to early mortality rates in people with severe mental illness. Health care professionals are encouraged to target the uptake of healthy behaviours, but there is limited guidance on how. The processes that cause or inhibit health behaviour change within interventions that use behaviour change techniques by health care practitioners are unclear. What does the study add? Staff and patients suggested that behaviour change techniques (BCTs) in some cases increased capability, opportunity, and motivation to engage in healthy behaviours, but in other cases had variable success. Staff and patients reported that in some cases, motivation impacted health behaviour change and was in turn affected by psychological capability, social, and physical opportunity. Individualized behavioural assessments, flexible approaches to BCT application, involvement from patient peer support and different ways of targeting patient motivation may help to increase healthy behaviour changes in this population.